Skin care interventions and early complementary food introduction for the prevention of atopic dermatitis in infants - Kupkina , Anna; Mozyrska, Olena (The Ukrainian Scientific Medical Youth Journal, 2023)
аtopic dermatitis and food allergy are common diseases that usually begin in early childhood and can occur together in the same individuals. The aim of this study was to assess the significance of interventions such as skin care products for the skin barrier improvement, breastfeeding and early complementary foods introduction for the primary prevention of atopic dermatitis and food allergy in infants by building logistic regression models. We performed a survey of 97 parents of children. The survey was conducted with the help of Google forms and distributed on the Internet. Method of building and analysing logistic regression models was used to analyse the association of the risk of atopic dermatitis in children with the factor characteristics. Characteristics were as follows: "Skin care 1: application moisturizers to the infant's skin", "Skin care 2: bathing infants with water containing moisturizing substances or moisturizing oils", "Skin care 3: usage of less soap, bathing the child less often", "paternal history of atopy", "duration of breastfeeding less than 1 year", "early introduction of supplementary food (up to the 6th month of life)". We obtained the following results: 42.2% of respondents reported about the application of moisturizing cream, parents of 16.5% of children were using moisturizing oil for bathing the child, 12.4% of parents used less soap and bathed the child less often, 28.9% reported that they were not using any interventions. It was established that when applying care method 1, namely applying moisturizing agents to the infant’s skin, the risk of developing atopic dermatitis increases, OR=12.8 (95% CI 3.89 - 42.3) (p<0.0001). When constructing a three-factor logistic regression model for predicting the risk of food allergy, no dependence was found between the development of food allergy and the presence of allergic diseases in parents, the period of introduction of complementary foods, and the duration of breastfeeding. Thus, this study did not reveal the protective role of skin care products, breastfeeding, and early introduction of complementary foods for the development of atopic dermatitis and food allergies in children. Multivariate analysis showed that atopic dermatitis is associated with emollients application to the infant’s skin. The use of moisturizing creams for the treatment of already existing atopic dermatitis or the path of percutaneous sensitization to allergens could have influenced the data.